ANALISIS IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PERSPEKTIF PEDAGOGIK PROFETIK DI SEKOLAH DASAR ISLAM DIAN DIDAKTIKA - Khofifah Tussholihah, - (2022)
The character building of students is well directed and continuously able to support the development of successful education, based on this, the implementation of character education during elementary school, this is in line with the level of moral development based on the Kohlberg theory that children obey the rules to avoid punishment, to create social order and respect society. Education is not only sharing knowledge, but there is a formation of character and attitude, in order to form a good attitude for the next generation. In accordance with Islamic teachings character education exemplifies the praiseworthy qualities of the Prophet Muhammad SAW, a good example suri for his people which includes Shidiq, Tabligh, Amanah, and Fatanah, Prophetic pedagogic concepts provide an explanation of educational science that is adapted to the teachings of Islam and the Prophet Muhammad SAW. In this case the implementation of character education is viewed from a prophetic pedagogical perspective, how schools transmit Islamic teachings not from theory alone but from habituation, behavior and carkater values applied in schools, both in the form of programs of concern to the surrounding community, character student program, Charity For Care Friday, Budaya 5S (Smile, Greet, Greeting, Polite, Gratitude), how teachers pay attention to the custom of dressing in the school environment, teachers and school employees become examples in habituation of character education formation in the school environment. The cultivation of character values is not only intended for students, but teachers also instill character values that will be applied to students, because all teachers are ethics teachers.-----Pembentukan karakter peserta didik diarahkan dengan baik dan berkelanjutan mampu mendukung pembangunan pendidikan yang berhasil, berdasarkan hal tersebut pentignya implementasi pendidikan karakter ketika masa Sekolah Dasar, hal ini sejalan dengan tingkatan perkembangan moral berdasarkan teori kohlberg anak menaati aturan agar terhindar dari hukuman, untuk terciptanya ketertiban sosial dan menghargai masyarakat. Pendidikan bukan hanya berbagi Ilmu, melainkan terdapat pembentukan karakter dan sikap, agar terbentuknya sikap yang baik untuk generasi selanjutnya. Sesuai dengan ajaran Islam pendidikan karakter meneladani sifat-sifat terpuji Rasulullah SAW, suri teladan yang baik bagi umatnya yang mencakup Shidiq, Tabligh, Amanah, dan Fatanah, konsep pedagogik Profetik memberikan penjelasan ilmu mendidik yang disesuaikan dengan ajaran Islam maupun Rasulullah SAW. Dalam hal ini implementasi pendidikan karakter ditinjau dari perspektif pedagogik profetik, bagaimana sekolah menularkan ajaran-ajaran keislaman tidak dari teori saja melainkan dari pembiasaan, perilaku dan nilai-nilai karkater yang diterapkan di sekolah, baik berupa program kepedulian kepada masyarakat sekitar, program murid karakter, Amal Jumat Peduli, Budaya 5S (Senyum, Sapa, Salam, Santun, Syukur), bagaimana guru memperhatikan adab berpakaian di lingkungan sekolah, guru dan karyawan sekolah menjadi contoh dalam pembiasaan pembentukan pendidikan karakter di lingkungan sekolah. Penanaman nilai karakter tidak hanya diperuntukkan siswa, melainkan guru ikut menanamkan nilai-nilai karakter yang akan diterapkan ke siswa, karena semua guru adalah guru budi pekerti.